Curbing cost overruns in infrastructure investment: Has reference class forecasting delivered its promised success? - Park, Jung Eun (European Journal of Transport and Infrastructure Research, 2021)
Infrastructure projects around the world have long been notorious for exceeding their budgets. To address persistent cost overruns, the American Planning Association urged planners to adopt reference class forecasting alongside traditional methods but the practice has not caught on in the U.S. Conversely, the U.K. adopted Kahneman’s Nobel Prize-winning theory to challenge biases in human judgment and mandated reference class forecasting for major projects in 2003. Has reference class forecasting, originally developed to rectify honest mistakes, brought the promised success in the public sector wherein political pressure is significant? Through before-and-after and with-and-without comparisons of 107 major projects, this empirical study examines the practical relevance of reference class forecasting for infrastructure investments. A before-and-after comparison reveals that the average cost overrun declined from 38% to 5% following the introduction of reference class forecasting. A with-and-without comparison also demonstrates that the U.K. surpassed its targeted probability of completing projects within budget by 12% using reference class forecasting, whereas the U.S. underperformed by 17%. Thus, reference class forecasting has engendered notable improvements in estimation in the U.K. This empirical study demonstrates the benefits of supplementing or replacing the current forecasting method. The findings can be used to reduce substantial financial risks for the government as well as social and economic welfare losses for society.